2017
DOI: 10.1590/1809-4392201602474
|View full text |Cite
|
Sign up to set email alerts
|

Metacercariae of Austrodiplostomum compactum (Lutz, 1928) (Trematoda, Diplostomidae) infecting the eyes of Plagioscion squamosissimus (Heckel, 1840) (Perciformes, Scienidae) from Lake Catalão, Amazonas, Brazil

Abstract: Austrodiplostomum compactum is a digenetic trematode whith metacercariae that occur in the eyes of a wide variety of fish species. In Brazil, A. compactum metacercariae have been reported in many fish species, but there are only a few studies in the Amazon region. Due to the lack of information in the Amazon, the aim of this study was to report the occurrence of A. compactum metacercariae in the eyes of 15 specimens of Plagioscion squamosissimus from the Lake Catalão, in Amazonas, Brazil. Fishes were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…The measurements of Austrodiplostomum spp. from this study were similar to those described by ALBUQUERQUE et al (2017) for P. squamosissimus from the western Amazon region. PINTO; MELO (2013) found that the morphometric measurements of A. compactum metacercariae obtained from experimentally infected Cyprinus carpio were similar to those from other fish.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The measurements of Austrodiplostomum spp. from this study were similar to those described by ALBUQUERQUE et al (2017) for P. squamosissimus from the western Amazon region. PINTO; MELO (2013) found that the morphometric measurements of A. compactum metacercariae obtained from experimentally infected Cyprinus carpio were similar to those from other fish.…”
Section: Discussionsupporting
confidence: 91%
“…with A. compactum infection in the eyes (ZICA et al, 2011). However, high levels of A. compactum infections have been reported for P. squamosissimus from Paraná River, in the São Paulo state (SANTOS et al, 2002) and Catalão Lake, in the state of Amazonas (ALBUQUERQUE et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A series of 12 metric dimensions were taken from 13 metacercariae specimens. Morphological characterization followed the methods of Santos et al (2002 ), Kohn et al (1995 ), Novaes et al (2006 ) and Albuquerque et al (2017 ). Samples were deposited in the Helminthological Collection of the Amazon National Research Institute (INPA).…”
Section: Methodsmentioning
confidence: 99%
“…Estas infecções podem provocar diminuição do crescimento e da sobrevivência do peixe, além de alterações morfológicas, que os tornam repugnantes, podendo atuar como potenciais vetores de outras infecções, além da possibilidade de transmissão para o homem (potencial zoonótico) e outros animais(KOHN et al, 2013). Estas metacercárias podem alterar o comportamento dos peixes(SEPPÄLÄ et al, 2004) e a formação de catarata é mais intensa depois que os parasitos completam seu desenvolvimento e estão prontos para infectar o hospedeiro final, aumentando a susceptibilidade do hospedeiro à predação(ALBUQUERQUE et al, 2017), sendo este, um método de transmissão altamente eficiente desses parasitos(MOURITSEN & POULIN, 2003). Annakohniella travassosi, parasitando Rhapiodon vulpinus Spix & Agassiz provenientes do rio Capivara, um tributário do Rio Tocantins.Potamotry gonhenlei (Castelnau) no rio Tocantins, no estado do Pará.Um filo bastante representantivo é Nematoda, que inclui um grande grupo de organismos cilíndricos, alongados, afilados em ambas as extremidades e de simetria bilateral.…”
unclassified